2016
DOI: 10.1007/s00204-016-1706-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of surface functionalization on the pulmonary inflammogenicity and translocation into mediastinal lymph nodes of graphene nanoplatelets in rats

Abstract: Graphene, a two-dimensional monocrystalline layer of carbon atoms, has potential in many applications not only in material sciences, but also in the biomedical fields, but there is little information about the role of surface modification on the toxicity of graphene-based nanomaterials. Here, we evaluated the role of surface functionalization of the graphene nanoplatelets (GNPs) on the pulmonary inflammogenicity and translocation into mediastinal lymph nodes using a rat intratracheal instillation model. Six ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…We also the checked the dynamic light scattering based size and zeta potential by Zetasizer Nano ZS (Malvern Instruments Limited, Malvern, UK). The process was previously reported (Cho et al, 2013;Lee et al, 2017a). N-acetyl cysteine (NAC) and β-actin antibody were purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…We also the checked the dynamic light scattering based size and zeta potential by Zetasizer Nano ZS (Malvern Instruments Limited, Malvern, UK). The process was previously reported (Cho et al, 2013;Lee et al, 2017a). N-acetyl cysteine (NAC) and β-actin antibody were purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…10 Among the investigated GBMs, on evaluating inflammatory cells and/or inflammatory markers in the bronchoalveolar lavage fluid as indices of lung inflammation, GO appeared to be the most toxic one compared to rGO, GNP or FLG, which appeared to be the least toxic GBM at the pulmonary level. [10][11][12][13][14][15][16][17] In contrast, in a very recent comparative study in male C57BL/6 mice (8 weeks-old), pharyngeal aspiration of GO induced lower toxic effects than rGO. 18 However, it should be noted that the physicochemical properties of the tested materials are not always completely reported in these studies (Table 1), making a direct comparison of the effects of GBMs difficult.…”
Section: Respiratory Exposurementioning
confidence: 99%
“…Another pulmonary in vivo study which compared six different surface modifications of GP showed increased oxidative stress and acute inflammation [35]. Moreover, positively-charged GP also showed significant inflammation characterized by the accumulation of neutrophil granulocytes [31]. On the other hand, single-layered graphene oxide platelets did not cause acute cytotoxicity or inflammation in a 3D human lung model and similarly, no acute toxicity was demonstrated after 28 days of in vivo exposure to multi-layered graphene platelets [29,36].…”
Section: Introductionmentioning
confidence: 96%
“…These non-biodegradable materials could pose a risk, especially for the respiratory system after exposure by inhalation [28]. It has been confirmed that GP, which are up to 25 µm in diameter, can be delivered beyond the ciliated airways and deposited in alveoli, where they can either persist in intercellular spaces, or are internalized by alveolar macrophages [29][30][31]. This may lead to inflammation, disruption of homeostasis, and subsequent fibrosis and tissue damage [28,[32][33][34].…”
Section: Introductionmentioning
confidence: 98%